Genetic diversity of endosymbiotic bacteria Wolbachia infecting two mosquito species of the genus Eretmapodites occurring in sympatry in the Comoros archipelago - Gomard, Yann; Hafsia, Sarah; Lebon, Cyrille; Rabarison, Patrick; Idaroussi, Ambdoul-bar; Yssouf, Amina; Boussès, Philippe; Mavingui, Patrick; Atyame, Célestine (Frontiers in Microbiology, 2024)
The influence of Wolbachia on mosquito reproduction and vector competence has led to renewed interest in studying the genetic diversity of these bacteria and the phenotypes they induced in mosquito vectors. In this study, we focused on two species of Eretmapodites, namely Eretmapodites quinquevittatus and Eretmapodites subsimplicipes, from three islands of in the Comoros archipelago (in the Southwestern Indian Ocean). Using the COI gene, we examined the mitochondrial genetic diversity of 879 Eretmapodites individuals from 54 sites. Additionally, we investigated the presence and genetic diversity of Wolbachia using the wsp marker and the diversity of five housekeeping genes commonly used for genotyping through Multiple Locus Sequence Typing (MLST). Overall, Er. quinquevittatus was the most abundant species in the three surveyed islands and both mosquito species occured in sympatry in most of the investigated sites. We detected a higher mitochondrial genetic diversity in Er. quinquevittatus with 35 reported haplotypes (N=615 specimens, Hd = 0.481 and π = 0.002) while 13 haplotypes were found in Er. subsimplicipes (N=205 specimens, Hd = 0.338 and π = 0.001), this difference is likely due to the bias in sampling size between the two species. We report for the first time the presence of Wolbachia in these two Eretmapodites species. The prevalence of Wolbachia infection varied significantly between species, with a low prevalence recorded in Er. quinquevittatus (0.8%, N=5/627) while infection was close to fixation in Er. subsimplicipes (87.7%, N=221/252). Both male and female individuals of the two mosquito species appeared to be infected. The analysis of MLST genes revealed the presence of two Wolbachia strains corresponding to two new strain types (STs) within the supergroups A and B, which have been named wEretA and wEretB. These strains were found as mono-infections and are closely related, phylogenetically, to Wolbachia strains previously reported in Drosophila species. Finally, we demonstrate that maternal transmission of Wolbachia is imperfect in Er. subsimplicipes, which could explain the presence of a minority of uninfected individuals in the field.